Registered nurses’ attitude and willingness to precept nursing students in Jamaica - Roper Carty MSN, Michelle; LM Lindo PhD, Jascinth; Stennett MPH, Rosain (International Journal of Advanced Nursing Studies, 2019)
Background: Registered nurses’ willingness to precept nursing students is an important factor in ensuring a positive clinical learning environment. However, in resource poor settings with high patient to nurse ratio and other challenges in the delivery of nursing care preceptorship may represent an additional challenge.Aim: To determine the willingness of registered nurses to precept student nurses in Jamaica; their attitude towards the paired preceptorship model and factors which may influence the precepting process.Design: This descriptive cross-sectional study utilized a 32-item self-administered questionnaire to collect data from 76 full-time registered nurses assigned to medical/surgical wards at a major teaching hospital.Results: Nurses had a positive attitude towards precepting (97%) and believed their actions and attitudes positively influenced the learning outcomes of students. Two-thirds of registered nurses (63%) were willing to precept students and 87% preferred the paired preceptorship model. Self-efficacy (p